Interpretation of the City Walls: Venice and Parma from Above (diségno, 2023)
Representing the shape of the city means fixing the physical consistency of a reality related to a certain time, through the knowledge of authors who over the centuries have tried to reconstruct the complex form of the city, representing it from above, simulating a point of observation without a doubt privileged and absolutely ideal. Venice and Parma are selected to explain the image of the city through authors who have recorded graphically from above, among other elements, the boundaries between nature and artifice. The parallel and compartmentalized narration is articulated through the reading of Jacopo de’ Barbari’s bird’s eye view of Venice (1500) and Paolo Ponzoni’s bird’s eye view of Parma (1572). In fact, in this period, a particular urban iconographic representation is adopted, the ‘planimetric perspective’, obtained from a plan made following a geometric survey, so that the perimeter of the walls and the road plot appeared in all their completeness; the buildings are instead depicted with the perspective, described from a point of view located at variable height above the horizon. The growing attention of cartographers and designers towards the city is linked to the new type of state organization that considers the city as a functional entity enclosed within the walls, whose view from above allows us to understand its consistency and peculiarities.
Keywords: perspective iconography; image; city; urban walls; city doors